Tracheal Extubation of Anesthetized Pediatric Patients with Heart Disease Decreases the Incidence of Emergence Agitation: A Retrospective Study - Kunigo, Tatsuya (Ann Card Anaesth, 2020)
BACKGROUND: Emergence agitation for pediatric patients after general anesthesia is one of the postoperative complications. The relationship between consciousness at tracheal extubation and emergence agitation is not clear. AIM: The aim of the present study was to determine whether tracheal extubation of anesthetized pediatric patients with heart disease by propofol decreases the incidence of emergence agitation. SETTINGS AND DESIGN: This was a retrospective case-control study conducted at a children's hospital. MATERIALS AND METHODS: Pediatric patients with heart disease aged 0-14 years who underwent cardiac catheterization under general anesthesia by propofol between October 2014 and September 2018 were enrolled. The incidence of emergence agitation by anesthetized extubation was compared with that by awake extubation. STATISTICAL ANALYSIS USED: Logistic regression analysis was performed. RESULTS: Anesthetized extubation was performed in 202 patients and awake extubation was performed in 56 patients. The incidence of emergence agitation was significantly lower in patients who underwent anesthetized extubation than in patients who underwent awake extubation (25.2% vs. 69.6%, P = 0.000). In logistic regression analysis, anesthetized extubation [odds ratio (OR): 0.075, 95% confidence interval (CI): 0.034-0.165, P = 0.000] and older age (OR: 0.808, 95% CI: 0.728-0.897, P = 0.000) were associated with a decreased incidence of emergence agitation, and preoperative anxiety (OR: 2.220, 95% CI: 1.060-4.660, P = 0.03) was associated with an increased incidence of emergence agitation. CONCLUSIONS: Tracheal extubation under anesthesia by propofol decreases the incidence of emergence agitation in pediatric patients with heart disease.